2020
DOI: 10.1039/c9mo00163h
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression and alternative splicing of mouse genes during spermatogenesis

Abstract: Considering the high abundance of spliced RNAs in testis compared to other tissues, it is needed to construct the landscape of alternative splicing during spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…While these genes have not been previously studied in spermatogenesis, scRNAseq data confirmed their expression in germ cell development. Surprisingly, while abundant expression of lincRNAs and alternatively spliced RNAs has been described for the testes, the use of alternative promoters during spermatogenesis has not been studied in mammals 91, 92 . In Drosophila , the transition from proliferating spermatogonia to differentiating spermatocytes is accompanied by dramatic change in transcription, with about a third of new transcripts originating from alternative promoters 93 .…”
Section: Discussionmentioning
confidence: 99%
“…While these genes have not been previously studied in spermatogenesis, scRNAseq data confirmed their expression in germ cell development. Surprisingly, while abundant expression of lincRNAs and alternatively spliced RNAs has been described for the testes, the use of alternative promoters during spermatogenesis has not been studied in mammals 91, 92 . In Drosophila , the transition from proliferating spermatogonia to differentiating spermatocytes is accompanied by dramatic change in transcription, with about a third of new transcripts originating from alternative promoters 93 .…”
Section: Discussionmentioning
confidence: 99%
“…Spliceosome. During spermatogenesis, the transcriptionally active germ-cell stages are the mitotic and meiotic stages and alternative splicing controls the temporally specific use of transcripts required for spermiogenesis 82 including, in partic- ular, meiotic intron-retaining transcripts mechanisms. 60 Eightyfour factors involved in the spliceosome pathway were found in the present analysis with a large majority of proteins showing a higher abundance in zone A (Figure 8).…”
Section: Enriched Pathwaysmentioning
confidence: 99%
“…However, a study of glomerular transcriptomes in patients has revealed that up-regulated genes in FSGS were involved in, among other things, spermatogenesis and gamete generation, and related for example to cell cycle and proliferation, TGF-β superfamily signaling and RNA process-80 Cluster 5 appeared to be characterized by translation and mRNA processing, including mRNA splicing, in all of the five biological categories, which is in accordance with the fact that factors controlling spermatogenesis are controlled at transcriptional and post-transcriptional levels, resulting in male germ cells expressing the widest array of transcript variants. 59,60,81,82 According to the heatmap profile of cluster 5, actors in mRNA processing exhibit a higher expression level in the zone of cysts with spermatogonia, then levels decreased during spermatogenesis to be at the lowest in the zone of late spermatids.…”
Section: Variations In Protein Levels During Spermatogenesismentioning
confidence: 99%
“…PTBP1 is highly expressed in spermatogonia during mitosis, while PTBP2 is significantly upregulated during spermatocyte meiosis. Abnormal changes in these two genes can lead to abnormal spermatogenesis [60,61]. For the first time, we have identified in human spermatozoa samples a splice variant of DDX46, a key gene in reproductive function regulation, which is generally thought to affect type I interferons and related pro-inflammatory cytokines by recruiting m6A "eraser" ALKBH5 [62,63].…”
Section: Frequent Alternative Splicing Events Especially Exon Skippingmentioning
confidence: 99%